Whose agenda is it? Regulating health research ethics in Labrador - Brunger, Fern; Bull, Julie (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2011)
In Labrador, the NunatuKavut (formerly Labrador Inuit Métis) have begun to introduce a rigorous community-based research review process. We conducted a study with leaders and health care workers in and beyond the NunatuKavut community of Labrador, asking them what should be emphasised in a community review. We also sought to identify whether and how community review should be distinct from the centralised, “institutional” research ethics review that would be the mandate of Newfoundland and Labrador’s impending provincial health research authority. In this article we report on our findings with the aim of providing strategies and direction for researchers, research ethics boards, and Aboriginal communities dealing with dual-level ethics review. We argue for the adoption and use of a consistent label for community review of research (“Community Research Review Committee”) as distinct from research ethics boards. We provide suggestions for the development of separate roles and responsibilities for community review of research to ensure that its tasks are clearly understood and delineated. Our objective is to promote a form of community research review, distinct from the “ethics” review of research ethics boards, that explicitly attends to research in the context of ongoing colonialism, assimilation, and exoticism.